2008
DOI: 10.4049/jimmunol.181.1.109
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Old Paradigm Challenged: Old Baboons Generate Vigorous Humoral Immune Responses to LcrV, A Plague Antigen

Abstract: Immune senescence in the elderly results in decreased immunity with a concomitant increase in susceptibility to infection and diminished efficacy of vaccination. Nonhuman primate (NHP) models have proven critical for testing of vaccines and therapeutics in the general population, but a model using old animals has not been established. Towards that end, immunity to LcrV, a protective antigen from Yersinia pestis, was tested in young and old baboons. Surprisingly, there was no age-associated loss in immune compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…IgG3, IgG4 and IgE responses were not detectable. Similarly in vaccination studies using Plague antigen LcrV in baboons [38], and in our previous studies with Sm-p80-pcDNA3 [14], IgG3 and IgG4 were found to be under the detection limits. However it is possible that the non-detection of IgG3 and IgG4 (and IgE) could be due to the poor cross-reactivity of human reagents being used for the detection of baboon antibody subtypes since no host-specific secondary antibodies from nonhuman primate origin are available for these subtypes [14].…”
Section: Discussionsupporting
confidence: 65%
“…IgG3, IgG4 and IgE responses were not detectable. Similarly in vaccination studies using Plague antigen LcrV in baboons [38], and in our previous studies with Sm-p80-pcDNA3 [14], IgG3 and IgG4 were found to be under the detection limits. However it is possible that the non-detection of IgG3 and IgG4 (and IgE) could be due to the poor cross-reactivity of human reagents being used for the detection of baboon antibody subtypes since no host-specific secondary antibodies from nonhuman primate origin are available for these subtypes [14].…”
Section: Discussionsupporting
confidence: 65%
“…Blood was collected from 33 females and 5 males ranging in age from 6 to 26 years old with a mean age of 14 years. It is estimated that this baboon age range would correspond to a human age range of approximately 18–78 years old [18], [19]. The average lifespan of baboons in captivity is approximately 21 years of age [20] and our population included 14 young adult (<13 years), 14 middle aged (13–17 years), and 10 aged baboons (>17 years).…”
Section: Methodsmentioning
confidence: 99%
“…The range of species in which the V antigen or F1/V vaccine combination has been evaluated is constantly growing, and now includes data generated in Old World non-human primates [71][72][73][74][75][76][77][78], as evidence is collected to achieve regulatory approval. The immunogenicity and efficacy data reported to date from these models are summarized in Table 2.…”
Section: Evidence For the Protective Efficacy Of F1 And V In Animal Mmentioning
confidence: 99%